2022
DOI: 10.3390/toxics10030124
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fractionation in Environmental Studies of Potentially Toxic Particulate-Bound Elements in Urban Air: A Critical Review

Abstract: In recent years, studies of heavy metal air pollution have increasingly gone beyond determining total concentrations of individual toxic metals. Chemical fractionation of potentially toxic elements in airborne particles is becoming an important part of these studies. This review covers the articles that have been published over the last three decades. Attention was paid to the issue of atmospheric aerosol sampling, sample pretreatment, sequential extraction schemes and conditions of individual extractions. Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 90 publications
(530 reference statements)
0
11
0
Order By: Relevance
“…In the Tessier procedure, the oxide fraction is extracted at a higher temperature, which increases the amount of metals bound with the Fe-Mn oxide fraction but may also mobilize metals bound with organic matter and sulfides. This problem does not occur with the SM&T procedure where the extraction is performed at room temperature (≈20°C) (Rao et al 2008(Rao et al , 2010Świetlik and Trojanowska 2008).…”
Section: Comparison Of Two Speciation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tessier procedure, the oxide fraction is extracted at a higher temperature, which increases the amount of metals bound with the Fe-Mn oxide fraction but may also mobilize metals bound with organic matter and sulfides. This problem does not occur with the SM&T procedure where the extraction is performed at room temperature (≈20°C) (Rao et al 2008(Rao et al , 2010Świetlik and Trojanowska 2008).…”
Section: Comparison Of Two Speciation Proceduresmentioning
confidence: 99%
“…Currently, speciation techniques are used to assess metal fractions in bottom sediment, soil, sewage sludge, compost, ash, waste and others. Speciation analysis is important especially when assessing the suitability of waste for agrotechnological use (Förstner 1993;Świetlik and Trojanowska 2008). However, for wastes that are landfilled or destined for reuse, one-step extraction with the use of one eluent under controlled conditions is most commonly used (Rao et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In aerosol precipitation, Cd is mainly represented by oxides (up to 71%) [ 3 ]. It was found that in solid fine atmospheric particles with a diameter of 2.5 to 10 μm (PM 2.5 –PM 10 ), the proportion of Cd mobile forms (including those extracted with weak acetic acid) reaches 50% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is an environmental toxicant of worldwide public health significance because numerous population-based studies suggest that exposure to Cd even at low levels adversely impacts the functions of most organs of the body [ 1 ]. Volcanic emissions, biomass and fossil fuel combustion, and cigarette smoke are sources of environmental Cd pollution [ 2 , 3 , 4 , 5 , 6 ]. Cd in cigarette smoke as a volatile metallic form and oxide (CdO) has a particularly high transmission rate [ 7 ].…”
Section: Introductionmentioning
confidence: 99%